A functionally graded material disk and method for fabricating thereof. - Ali, Aidy; Sanuddin, Asmawi (2011)
The present invention relates to a functionally graded material disk comprising of metal and ceramic composite (100), characterised by: a core; and a plurality of concentric rings encircling the core including an outer ring and a plurality of inner rings of varying proportions of ceramic to metal. A method for fabricating a functionally graded material disk of metal and ceramic composite (200), comprising a core and a plurality of concentric rings of increasing proportions of ceramic to metal, characterised by the steps of: firstly, mixing metal and ceramic in powder form to form a plurality of mixtures of varying percentage of metal and ceramic by volume; then, casting the plurality of mixtures in a plurality of concentric rings and a core to form a circular disk; then, compressing to compact said circular disk; and then, heating said circular disk to below the melting temperature of the metal or the ceramic for sintering the disk inside a furnace; then, cooling said circular disk inside the furnace.